Homecare: a study on its implementation in a private health system - Soerensen, Andrea Alves; Mendes, Isabel Amélia Costa; Hayashida, Miyeko (Rev Rene, 2004)
This is the study of a case about the implantation of a homecare programme in a hospital in Ribeirão Preto. It was carried out with the objective of identifying how and why this kind of assistance has been implemented in private health services. Interviews with the nursing coordinator and the administrative manager, responsible for the service, were made. The analysis of the data collected allowed the assessment of positive and relative points that the practice of homecare provides. It could be seen that several service goals were reached almost immediately, which makes us believe more and more in the importance of this type of assistance, which benefits everyone, those who deliver it as well as those who receive it.